Arbuscular mycorrhizal fungi as a biological soil management practice for regulating soil carbon dynamics in agricultural soils: A global meta-analysis - Huawei Yang; Yuhang Zhang; Dingyi Liu; Yue Fan; Diwei Song; Pengju Li; Jingdan Yang; Xiaozhe Ma; Ruixin Bi; Shumin Li; Lingbo Meng (Soil and Tillage Research, 2026)

The effects of spark plugs and lubricant oils on pre-ignition combustion in a hydrogen fueled engine - An Lu; Peng Yin; Benzheng Fan; Kuicong He; Xiaogang Yang; Yuan Bi; Xiaowei Hao; Yao Li; Huimu Yang; Dong Han (Fuel, 2026)

Enhanced simultaneous nitrogen and phosphorus removal via a step-feed anoxic/oxic process coupled with side-stream enhanced biological phosphorus removal - Ruoyu Wu; Dongqi Wang; Mengbo Huang; Yanzhe Gong; Guangxiang Duan; Jiayu Bi; Wengui Gu; Lu Qin; Yuan Guo; Xiaopeng Qiu; Yishan Lin; Da Kang; et al. (Journal of Environmental Chemical Engineering, 2026)

Highly efficient photoelectrocatalytic degradation of 2,4-dichlorophenol using Mo-doped BiVO4 photoanode - Jinfeng Zhi; Chunlan Lv; Lian Wang; Qiang Wang; Yujing Guo; Yingpu Bi; Lifang Fan (Journal of Environmental Chemical Engineering, 2026)

Comparison of key aroma active compounds in fresh and hot air dried Agaricus blazei by molecular sensory methods - Qinghui Jia; Yixin Dai; Ruiyang Chen; Fan Yang; Ye Liu; Shuang Bi (Food Research International, 2026)

Molecular mechanisms underlying umami taste perception: A DIA-based proteomic analysis of Agrocybe aegerita peptides - Yixin Dai; Qinghui Jia; Fan Yang; Shuang Sun; Jingzhe Sun; Yanbo Wang; Ye Liu; Shuang Bi (Food Chemistry, 2026)

Modulating local structural disorder in layered cathodes with alternating edge- and face-sharing octahedra for enhanced high-rate performance - Chengjun Fan; Xiaoxia Yang; Lingling Yao; Qin Wang; Xiao Ouyang; Leidang Zhou; Zhiwen Gao; Rui Jia; Xibang Chen; Jing Chen; Hao Liu; Bin Liao; et al. (Chemical Engineering Journal, 2026)

Tectonic forcing and climate modulation on the evolution of aeolian sediment provenance from the northeastern Tibetan Plateau margin to the Chinese Loess Plateau - Yuxin Fan; Minmin Gao; Fei Wang; Qingsong Cai; Chuanying Zhu; Xueyu Yan; Ke Bi; Qiang Shu; Ping Zhang (Quaternary Science Reviews, 2026)

A GWAS-Derived Histone H4 Variant Linked to Ear Row Number Reveals Functional Insights into the Maize ZmHistone Gene Family - Babar Ijaz; Fuyan Jiang; Yaqi Bi; Xingling Jiang; Xingming Fan (Plant Science, 2026)

Study on the removal of enrofloxacin from surface water by high sulfur coal/persulfate system - Yaru Zhang; Wenlong Bi; Bo Sun; Fenwu Liu; Shaozu Xu; Yashi Liu; Xinyu Fan; Yuyang Wang (Journal of Environmental Chemical Engineering, 2026)

Cold plasma technology for the modification and quality control of food components via exogenous RONS: Mechanisms, strategies, and future prospects - Xiaotong Fan; Jiabao Ni; Yanxiang Bi; Shiye Luo; Pingping Dong; Shenyuan Quan; Jiaxin He; Xiaoming Fang (Food Bioscience, 2026)

Covalent multidentate engineering tailored for advanced potassium-ion storage - Xinghui Sun; Gaobo Zhang; Hongyu Cao; Haohao Ding; Lize Zhang; Lingxia Fan; Aruuhan Bayaguud; Bangjun Wu; Hongwei Bi; Yelong Zhang (Chemical Engineering Journal, 2026)

Heterojunction interfacial Mo − S bond induced directional electron transport enables efficient visible-light-driven hydrogen evolution - Yidong Pan; Yufeng Fan; Yang Fu; Zhichao Deng; Muhammad Sohail Riaz; Hong Li; Weiju Hao; Jinchen Fan; Guisheng Li; Qingyuan Bi (Chemical Engineering Journal, 2026)

Genomic and genetic insights into the divergence between indica and japonica rice - Xiangxi Zhuansun; Wenlong Guo; Siqi Xia; Jun Shu; Kai Wang; Qiyu Zhang; Hao Wen; Lina Du; Siyu Wen; Ge Gao; Junran Wang; Dan Wang; et al. (Science Bulletin, 2026)

Beauvericin modulates immune responses in the silkworm, Bombyx mori: insights from cellular and transcriptomic analyses - Jinhua Fan; Yong Bi; Jia Li; Hui Su; Aiying Cheng; Baozhen Li (Journal of Invertebrate Pathology, 2026)

Insights into saltiness enhancement effect and processing stability of pea-derived peptides using psychophysics and molecular docking - Anzhen Fu; Yixin Dai; Fan Yang; Qinghui Jia; Ye Liu; Shuang Bi (Food Research International, 2026)

Quality-driven grinding control: Monitoring lipid oxidation markers for off-flavor mitigation in pea milk - Shuang Bi; Lichang Yan; Xiaoying Xiong; Fan Yang; Ye Liu (Food Control, 2026)

Pilot-scale treatment of wool scouring wastewater in two-stage anoxic/oxic moving bed biofilm reactor: Performance and nitrogen removal mechanism - Xing Fan; Xueqing Shi; Jiahua Wu; Wenxuan Qiu; Xifeng Zhao; Jiazhong Zhou; Wenjie Han; Hongrui Lu; Ling Wang; Xuejun Bi (Bioresource Technology, 2026)

Dynamic changes and functional analysis of the vaginal microbial communities in reproductively dysfunctional giant pandas - Xin Chen; Ling Dao; Wenjun Huang; Bi Li; Xiaolan Wang; Zhengyu Chen; Fangfang Liu; Li Luo; Fan Xu (The Veterinary Journal, 2026)

Characterization of the flavor profile in apricot extract by combining molecular sensory science and untargeted metabolomics - Shuang Sun; Jingzhe Sun; Ruiyang Chen; Yixin Dai; Fan Yang; Shuang Bi; Ye Liu (Food Bioscience, 2026)

Self-cleaning and anti-wetting MoO3@ZIF-8/PAES-CF3 nanofiber membrane enabling stable membrane distillation - Shu Bi; Huoying Tan; Shiqiang Liang; Fan Yang; Jiamei Xin; Wenbin Wang; Zhi Geng; Chi Wang (Desalination, 2026)

A digital microfluidics-based single-cell ddPCR platform for high-throughput gene copy number analysis applied to single cultured cells - Yicheng Sun; Jiancong Liang; Hui Li; Yechen Fan; Te Peng; Siyi Hu; Yuan Gao; Wenli Zhao; Ling Jiang; Khadija Urooj; Hanbin Ma; Mude Shi; et al. (Analytica Chimica Acta, 2026)

Study on prestack reservoir prediction of deep volcanic rock gas reservoirs in Chaganhua sub-sag of Songnan Fault Depression - Qin-lin Yang; Xue-pei Fan; Chen-chen Bi; Lan-mei Ke; Ye Yang; Da Zhang; Shu Wang (Applied Geophysics, 2026)

Geological sedimentary records constraining Earth-Moon system evolution over the past 60 million years: Insights from Cyclostratigraphy - Zhenwei Ge; Juye Shi; Quanyou Liu; Tailiang Fan; Zhiqian Gao; Huiyuan Xu; Ruyue Wang; Weihui Bi; Zhijun Jin (Gondwana Research, 2026)

Decoding salty peptides from pea protein: Isolation, characterization, and structure-activity relationship - Anzhen Fu; Jingzhe Sun; Shaobo Zhen; Fan Yang; Huanlu Song; Jinhua Zuo; Xiaoyan Zhao; Ye Liu; Shuang Bi (Food Chemistry, 2026)

Nitrogen‐Driven Acidification and Microbial Shifts Contribute to a Breakdown in Carbon–Phosphorus Trade in the Rhizosphere - Shuo Sun; Ruzhen Wang; Jordi Sardans; Mengjiao Bi; Ying Zhang; Xinyu Fan; Xiaoyu Guan; Yong Jiang; Mingkai Jiang; Xingguo Han; Josep Peñuelas (Global Change Biology, 2026)
Anthropogenic nitrogen (N) deposition is reshaping terrestrial phosphorus (P) cycling. This effect is pronounced in the rhizosphere, where plants respond to P status by releasing root exudates. Yet it remains unclear whether these interactions drive P mobilization or immobilization. To capture both the chronic effects of N deposition and the transient effects of root exudates, we integrated a decade‐long N addition experiment (a single annual application of (NH 4 ) 2 SO 4 at 0, 2, and 5 g N m −2 year −1 ) with a 14‐day laboratory incubation. Specifically, rhizosphere and bulk soils from a Eurasian meadow steppe were amended with 13 C‐labeled low‐molecular‐weight organic acids (LMWOA; a single addition of acetic and succinic acids). Phosphorus transformation was quantified using sequential extraction and 31 P NMR, while underlying mechanisms were assessed via priming effects, phosphatase activity, and microbial functional genes. Nitrogen enrichment promoted the dissolution of mineral‐bound inorganic P (P i ) through acidification (pH drop > 1 unit), leading to the accumulation of secondary mineral P i and organic P (P o ). This was accompanied by reduced microbial phosphatase activity and lower abundances of the P‐cycling genes phoC and phoD . The above effects were stronger in the rhizosphere than in bulk soil. In the rhizosphere, LMWOA enhanced microbial P immobilization and P o accumulation, even as their positive priming effects accelerated soil organic carbon mineralization. These results were partly driven by the recruitment of key P‐cycling taxa such as Burkholderia and Rhodoplanes , suggesting a shift in carbon‐for‐P exchange between plants and microbes under N deposition. Collectively, our findings indicated that while N‐induced P solubilization may temporarily alleviate P limitation, synergy with increased LMWOA exudation promotes P o accumulation. Though P o can be labile compared to mineral‐bound forms, suppressed phosphatase activity likely constrains its mineralization. This inhibition potentially decelerates P cycling, thereby compromising the medium‐ to long‐term P supply within the Eurasian steppe.

Dynamic behaviors of operational floating offshore wind turbines subjected to ship collisions - Xudong Ye; Xiaoqiang Yang; Wei Fan; Mindong Yang; Kaiming Bi (Ocean Engineering, 2026)

Algal ecological dynamics tracking model for studying hydrodynamic impacts on algae transport and accumulation in a shallow lake - Fei Du; Xiaobo Liu; Shiyan Wang; Chang Liu; Aiping Huang; Weijie Wang; Budong Li; Rui Gao; Xin Tian; Zhen Han; Hao Fan; Bi Wu (Journal of Hydrology, 2026)

Deciphering the mechanisms underlying cadmium tolerance in the endophytic fungus Trichoderma atroviride D16 - Xue-Wen Bi; Xing-Guang Xie; Wen-Jing Zhang; Rui-Di Zhang; Khalid Rahman; Xin-Zhu Yu; Cun-Yu Fan; Shu-Lang Ding; Yu-Qing Peng; Ting Han (Fungal Biology, 2026)

A coupled strain-damage framework for rock deformation and dynamic damage under cyclic loading based on mesoscale elastoplastic elements - Haohao Zhang; Rui Chen; Yazhou Wang; Huijie Bi; Chaojun Fan; Hui Peng (Computers and Geotechnics, 2026)

Meningitis due to pandrug resistant Chryseobacterium gleum: microbiological cure and clinical response with linezolid-based combination therapy - Leilei Wang; Yingmin Bi; Yu Zhou; Fan Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Ginkgolide B-cyclodextrin inclusion complexes: an encapsulation strategy for improved solubility and aerosol inhalation therapy in bronchial asthma - Yuying Wang; MingLi Wei; Yan Zhang; Yuxin Liu; Xiaoshuang Bi; Xingting Fan; Jingxin Gou; Haibing He; Xing Tang; Yu Zhang; Tian Yin (Drug Delivery and Translational Research, 2026)

Resource utilization of spent grains, an underutilized by-product from Chinese Baijiu brewing: Recent advances and prospects - Zhao Yang; Sheng Wang; Bi Chen; Fan Yang; Ping Xiang; Li Wang; Jianlong Wang (Resources, Conservation and Recycling, 2026)

Fabrication of corrosion-resistant superhydrophobic nickel‑cobalt layered double hydroxide coating on copper mesh for oil-water separation - Yufeng Liu; Mingzhe Bi; Ziqi You; Ruina Ma; Yongzhe Fan; An Du; Xue Zhao; Mingxu Yang (Journal of Water Process Engineering, 2026)

Effects of alkaline pretreatment on side-stream enhanced biological phosphorus removal and recovery process - Ruoyu Wu; Dongqi Wang; Yufan Wu; Lu Qin; Xiaonian Feng; Yi Xiao; Yanzhe Gong; Guangxiang Duan; Jiayu Bi; Zhiqiang Xu; Yuan Guo; Jiake Li; et al. (Journal of Water Process Engineering, 2026)

Bacterial assembly and succession during aerobic granulation stimulated by Fe3O4 nanoparticles with real municipal wastewater: The role of acyl-homoserine lactones mediated communication - Kailing Pan; Caixia Fang; Yuxuan Wei; Hengyuan Zhang; Di Wu; Jiazhong Zhou; Wenjie Han; Xiaoyan Fan; Ling Wang; Shujuan Huang; Xuejun Bi (Journal of Water Process Engineering, 2026)

Effects of metals on thermal oxidation of jet fuel and mitigation strategies - Bowang Lu; Xiaoyong Fan; Dong Li; Jun Yang; Long Yan; Bo Yang; Guanghui Pang; Jian Li; Bi Chen (Fuel, 2026)

Dissection of the genetic basis of 1392 rice landraces and 770 hybrid combinations reveals great potential of rice landraces in hybrid rice improvement - Yinting Wang; Zixuan Li; Bi Wu; Xueqiang Wang; Wenyan Yang; Danjing Lou; Jinyue Ge; Ziran Liu; Wenlong Guo; Neng Zhao; Jun Yang; Weiya Fan; et al. (Molecular Plant, 2026)

Probiotic strain identification and safety assessment of unlabeled bacteria in infant products - Nanlan Wang; Yarong Wu; Yang Liu; Qian Wen; Fan Bai; Yafang Tan; Yujun Cui; Xingyin Liu; Yujing Bi; Ruifu Yang; Peng Luo (International Journal of Food Microbiology, 2026)

Significantly enhanced effects of heavy metals on the toxicity, bioconcentration and biomagnification under combined exposure - Qian Cheng; Jin Zhang; Bi-ya Dai; Xin-yue Wang; Guang-zhen Ji; Yuan-fan Zhao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Dual role of functional bacterial agent based on Bacillus subtilis coupled with smooth vetch (Vicia villosa var.) on cadmium-contaminated soil: Synergistic passivation and nutrient supply - Qiwen An; Jie Liu; Yitong Liu; Fuxuan Bi; Zonghao Dong; Xu Liu; Zhao Jiang; Libo Fu; Hongli Fan; Jianhua Qu; Ying Zhang (Journal of Environmental Chemical Engineering, 2025)

Multivalent copper-carbon-catalyzed persulfate/O2 system: The relation between copper valence and the species of reactive oxygen - Zehui Fan; Zhisen Li; Dan Mo; Jingyang Zhang; Shuyi Yang; Yun Li; Changlong Bi; Chong Peng; Tao E (Journal of Environmental Chemical Engineering, 2025)

High-humidity hot air impingement blanching (HHAIB): A novel strategy to reconcile drying efficiency and quality preservation in edible cricket processing - Jiaxin He; Xiaotong Fan; Lei Li; Shenyuan Quan; Shiye Luo; Jiabao Ni; Yanxiang Bi; Na Li; Ruge Cao; Xiaoming Fang (Food Chemistry, 2025)

Multi-omics profiling delineates reheating-modality-driven flavor divergence in Yuxiang shredded pork - Xuan Wang; Shaoran Shi; Xiaomeng Wu; Shuang Bi; Fan Yang; Xiuli Du; Youyou Cheng; Jingguang Li; Yunfeng Zhao; Dawei Chen (Food Chemistry, 2025)

Effects of pH-shifting and ultrasound on the allergenicity and physicochemical properties of mung bean protein: application in gellan gum-based complex gels - Afsaneh Taheri; Chee Fan Tan; Xuezhi Bi; Felicia Ong; Fatin Natasha Binte Abdul Halim; Juan Du (Food Chemistry, 2025)

Polyimide sulfonyl group grafting and POSS crosslinking designs depress multi-scales charge transport for high-temperature capacitive energy storage - Zhen Li; Qianyi Fan; Yikun Dong; Xuefei Bi; He Gao; Yu Feng; Ji Liu (Chemical Engineering Journal, 2025)

Site-specific substitution strategy for poisoning-resistant of ZrCo-based hydrogen isotope storage alloys - Shunrui Xiao; Jiacheng Qi; Jiapeng Bi; Fei Chu; Qianwen Zhou; Xiulin Fan; Jiahuan He; Xingwen Feng; Huaqin Kou; Xuezhang Xiao; Tao Tang; Wenhua Luo; et al. (Chemical Engineering Journal, 2025)

Candidate genes for kernel ratio in maize identified via combined GWAS and QTL mapping across multiple environments - Fengli Ye; Ranjan K. Shaw; Babar Ijaz; Fuyan Jiang; Jiachen Sun; Tao Dai; Yaqi Bi; Xiaoli Hong; Xingming Fan (Theoretical and Applied Genetics, 2025)

Experimental and analytical model study on the process of sub-cooled water jetting from high-energy pipelines - Tao Zhang; Qincheng Bi; Miao Gui; Fan Feng; Zhaohui Liu; Teng Wang (Annals of Nuclear Energy, 2025)

Constitutive androstane receptor activation modulates YAP expression and activity through ubiquitination and sumoylation - Fengting Liang; Shuaishuai Zhang; Wenhong Zhou; Guofang Bi; Xiao Yang; Peng Wang; Shicheng Fan; Shuang Hu; Chenghua Wu; Xiaowen Jiang; Dan Li; Hui Ouyang; et al. (Toxicology Letters, 2025)

A novel approach for emergency action planning based on functional modeling and reasoning - Jun Yang; Shuxin Bi; Yipeng Fan; Mengchu Song (Process Safety and Environmental Protection, 2025)

Effects of Beauveria bassiana on immune responses in the silkworm, Bombyx mori: focus on haemocyte dynamics - Jinhua Fan; Lingzhi Wu; Xinxiang Fan; Zixiao Li; Guizhen Yuan; Yong Bi; Baozhen Li (Journal of Invertebrate Pathology, 2025)

Low-permeation resistance thin-film composite nanofiltration membrane based on high-precision 3D-printed support layer - Shiqiang Liang; Wenbin Wang; Tongyao Wu; Jinkai Zhang; Qindong Wang; Shu Bi; Fan Yang; Chi Wang; Zhi Geng; Zhongmin Su (Desalination, 2025)

A Raman-microfluidic system for single bacterium identification, and sorting, and its application in bacterial properties analysis - Zixin Shu; Xiaoyu Zhang; Fengyi Li; Yujing Bi; Xiangqian Liu; Weigang Ma; Aoran Fan; Xing Zhang (Analytica Chimica Acta, 2025)

Nuclearporin subcomplex Nup98/Rae1 is vital for maternal-to-zygotic transition during early embryonic development - Luo Anfeng; Gu Hao; Akhtar Ali; Qi Mengfan; Pan Kaixin; Zhou Changfan; Zeng Wei; Liu Song; Ren Hongyan; Bi Yanzhen; Chen Fan (Theriogenology, 2025)

The climate-driven mechanisms of sedimentary evolution in the mud area southwest off Cheju Island during the Holocene - Jingyi Cong; Huisong Fan; Shipu Bi; Xi Mei; Yanguang Dou; Zhonglei Wang; Ze Ning; Yong Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

NxO emission from a pure-MBBR system: Characteristics, influencing factors, bacterial community, and metabolism pathway - Xing Fan; Jianchang Wang; Xuyi Wang; Di Wu; Haicheng Liu; Xiaolin Zhou; Shujuan Huang; Jiazhong Zhou; Wenjie Han; Xiaoyu Liu; Tang Yang; Xuejun Bi (Journal of Environmental Chemical Engineering, 2025)

Janus architecture applied in organic photoelectrochemical transistor biosensors for superior selective direction recognition - Shanding Zhou; Peng Ju; Jingtian Chi; Fan Bi; Siyu Wen; Qingjun Feng; Xiaofei Yin; Bingshu Wang (Chemical Engineering Journal, 2025)

Microbially induced phosphate precipitation disentangles sludge retention time trade-off enabling efficient phosphorus removal with minimal sludge discharge in aerobic granular sludge - Peng Bi; Xiaohui Yan; Yueying Song; Hebin Miao; Hui Sun; Ying Han; Long Chen; Kangxin Yan; Mingyang Li; Fan Xiong; Jingwei Ma; Qiulai He (Chemical Engineering Journal, 2025)

Is green algae polysaccharide a ‘green path’ to health? - Sammueal Ong Jun Kai; Matthew Myint; Chee Fan Tan; Yi Fan Hong; Meiyappan Lakshmanan; Ying Swan Ho; Thomas T. Wheeler; Xuezhi Bi; Ian Walsh; Sean Chia; Kuin Tian Pang (Algal Research, 2025)

Singlet oxygen-driven non-radical oxidation of phenylurea herbicides in aqueous environment: Reaction behaviors and degradation mechanisms via unactivated PMS systems - Zi-Han Feng; Lin-Hao Xu; Fu-Xiang Tian; Fan Lai; Jing Ye; Yu-Qiong Gao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2025)

Characterization of key aroma compounds in Maillard reaction products of Agrocybe aegerita enzymatic hydrolysates by GC×GC-O-MS - Hongyang Meng; Fan Yang; Shaobo Zhen; Anzhen Fu; Shuang Bi; Ye Liu (Food Bioscience, 2025)

A recyclable magnetic polyethyleneimine-functionalized cellulose aerogel for reducing cadmium (Cd) accumulation in acidic contaminated soil: Stress mitigation and soil improvement mechanisms - Fuxuan Bi; Zhao Jiang; Zhiyu Zhang; Zhan Zhang; Mengning Wang; Libo Fu; Hongli Fan; Jianhua Qu; Ying Zhang (Chemical Engineering Journal, 2025)

Identification of key candidate genes regulating hundred-grain weight in the maize inbred line Ye107 from Southern China - Xiaoli Hong; Ranjan K. Shaw; Fuyan Jiang; Jiachen Sun; Yaqi Bi; Xiao Wu; Tao Dai; Fengli Ye; Jiaguo Zhu; Tingting Guan; Chunxia Xu; Xingming Fan (Plant Cell Reports, 2025)

Discrimination of tea varieties and bud sprouting phenology using UAV-based RGB and multispectral images - Litao Sun; Jiazhi Shen; Yilin Mao; Xiaojiang Li; Kai Fan; Wenjun Qian; Yu Wang; Caihong Bi; Hui Wang; Yang Xu; Jingbiao Xu; Zhaotang Ding (International Journal of Remote Sensing, 2025)

Deciphering the Therapeutic Mechanisms of Wuzi Yanzong Pill for Asthenozoospermia: A Synergistic Approach Combining Bioinformatics and Molecular Dynamics - Zi-Hao Liu; Shuang-Yang Li; Bi-Jun Li; Fan Zhang; Xiang-Guang Li; Xuan Li; Jie Zheng (Cell Biochemistry and Biophysics, 2025)

Flavor enhancement pathways and mechanisms of cold-pressed walnut oil based on defatted cold-pressed walnut meal hydrolysates - Ying Xu; Yixin Dai; Shaobo Zhen; Fan Yang; Jihong Wu; Shuang Bi; Ye Liu (Food Chemistry, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Design-oriented efficient analysis method for steel-UHPC composite fenders with foam-filled steel tubes under vessel collisions - Qinglin Wu; Wei Fan; Jiatong Liu; Kaiming Bi; Zhiyong Wan (Engineering Structures, 2025)

Construction of 2D-2D heterojunctions of VN nanosheets within Ti3C2 nanosheets for improved flow-electrode capacitive deionization performance - Kang Yang; Wei-Bin Zhang; Juan Zhou; Huan Gou; Ashkar Batol; Fan Yang; Bi Chen; Xin-Yu Liu; Xue-Jing Ma (Desalination, 2025)

Bioactive multifunctional hydrogel to ameliorate adverse joint microenvironment and enhance cartilage regeneration - Zhang Po; Ma Xiao; Zhang Han; Liu Yang; Zhu Liang; Bi Yanchi; Wang YiHu; Shen Zhan; Wang Jian; Jiang Fan; Zhu Xuesai; Yao Yizhi; et al. (Chemical Engineering Journal, 2025)

The first mitogenome of Dracaena (Dracaena sp. in Guangxi) reveals complex multi-chromosomal architecture and long repeat sequence-driven evolution - Zihao Wang; Wei Zheng; Qi Fan; Jiale Guo; Yuxuan Zhang; Guiqi Bi; Peihong Shen; Luodong Huang (Tree Genetics & Genomes, 2025)

Membrane-associated NAC transcription factor MaNAC169 is a positive regulator during banana fruit ripening - Fan Liu; Xueli Sun; Jia He; Jingjing Shan; Ou Sheng; Tongxin Dou; Yaoyao Li; Weidi He; Qiaosong Yang; Chunhua Hu; Huijun Gao; Xinxiang Peng; et al. (Postharvest Biology and Technology, 2025)

Mechanistic insights into carbon black-activated AKT/TMEM175 cascade impairing macrophage-epithelial cross-talk and airway epithelial proliferation - Yawen Feng; Xiaowen Tang; Hongying Fu; Xiaobo Fan; Juntong Wei; Jianying Liu; Hongmei Wang; Huanhuan Bi; Ziyan Chen; Xiaoran Wei; Yuxin Zheng (Environmental Pollution, 2025)

Inhibition of KDM6B prevents osteoarthritis by blocking growth plate-like H3K27me3 loss in bivalent genes - Hao Du; Yao Zhang; Xi Yu; Xuanhe You; Diwei Wu; Ze Du; Yongrui Cai; Zhenyu Luo; Hanpeng Lu; Zhixin Liao; Bi-Sen Ding; Ya Zhao; et al. (Science China Life Sciences, 2025)

Oil Spill Occurrence and Pollution Risk Assessment Based on Sea State, Oil Platform Location, and Shipping Route Density in the Bohai Sea - Tao Liu; Ruichen Cao; Minxia Zhang; Xing Chen; Fan Bi; Jiangling Xu (Journal of Marine Science and Engineering, 2025)
The Bohai Sea is the only semi-enclosed inland sea in China. With active marine economic activities, it faces a persistently high risk of oil spill accidents. This study assesses the occurrence risk and pollution risk of oil spills by considering factors such as sea state, the location of oil platform, and shipping route density in the Bohai Sea. The results show that the central part of the Bohai Sea, the southern Liaodong Peninsula, and the Bohai Strait area have a relatively high occurrence risk of oil spills due to busy maritime traffic and harsh sea conditions. In contrast, some areas in the northern, western, and southern parts of the Bohai Sea have a relatively low occurrence risk of oil spills because of weak maritime activity intensity and relatively calm sea state. In terms of the oil pollution risk, its distribution in the Bohai Sea shows significant seasonal characteristics, which are mainly comprehensively affected by multiple dynamic factors such as circulation, monsoon, and seawater exchange. Based on the oil pollution risk distribution, seasonally targeted strategies are proposed, which can provide a scientific basis for oil spill prevention and emergency management in the Bohai Sea, and help relevant departments formulate targeted prevention and control strategies.

Spatial and Temporal Characteristics of Riverine Fungal Communities and Their Responses to Environmental Factors in China's Largest Jiang-Flavor Baijiu-Producing Region - Yufeng Xiao; Jianguo Zhou; Fengxue Wu; Fan Yang; Bi Chen; Zhibin Li; Yong Liu; Dengjun Wang; Jingfu Wang (Current Microbiology, 2025)

Mutation in FvPAL2 leads to light red strawberry fruits and yellow-green petioles - Chong Wang; Anqi Lin; Yankong Zhou; Zheng Liu; Peng Bai; Yuxuan Zhu; Junmiao Fan; Xiaoyi Bi; Huiyun Kuang; Hongli Lian; Pengbo Xu (Plant Science, 2025)

Enhanced remediation of cadmium-contaminated farmland by smooth vetch (Vicia villosa var.) coupled with phosphorus/sulfur co-doped biochar: Synergetic performance and mechanism - Fuxuan Bi; Zhao Jiang; Mengning Wang; Qiutong Lin; Xiaoyang Liu; Libo Fu; Hongli Fan; Weidong Cao; Jianhua Qu; Ying Zhang (Journal of Cleaner Production, 2025)

Interface molecular mineralization enables green, scalable fabrication of MOF-fabric composites - Yating Ji; Weifeng Yang; Xiaoyan Li; Zhuizhui Fan; Bi Xu; Zaisheng Cai (Journal of Cleaner Production, 2025)

Provenance of fine-grained Quaternary sediments in the Tengger Sandy Desert recorded by Sr-Nd isotopes and its linkage with Quaternary aeolian silts on the Chinese Loess Plateau - Yuxin Fan; Minmin Gao; Fei Wang; Qingsong Cai; Guangliang Yang; Chunlei Zong; Ke Bi; Xueyu Yan; Qiang Shu; Bowen Kong (Quaternary Science Reviews, 2025)

Microplastics in fish species from the eastern Guangdong: Implications to Indo-Pacific humpback dolphin (Sousa chinensis) and human health - Jinyan Liu; Qilin Gutang; Yingping Fan; Ran Bi; Puhui Zhao; Keqin Zhang; Zewei Sun; Ping Li; Wenhua Liu; Jianxin Wang (Marine Environmental Research, 2025)

Spatially isolated silver in graphitic carbon nitride matrix by Ag-supramolecular mixture pyrolysis for promoting 4-nitrophenol reduction - ZhanAo Lv; Fan Wu; Min Zhao; KaiYu Bao; TianHao Chen; ZhengKai Tao; ChangYan Huang; Tao Li; JiaJun Bi (Journal of Water Process Engineering, 2025)

Corrigendum to “Mesozoic–Cenozoic exhumation of the giant Jinchuan Ni-Cu sulfide deposit, China: Evidence from single-grain apatite (U-Th)/He ages” [J. Asian Earth Sci. 271 (2024) 106231] - Qingsong Cai; Xueyu Yan; Yuxin Fan; Minmin Gao; Guangliang Yang; Ke Bi; Ying Wang; Chuanying Zhu; Mingjie Zhang; Xiaohu Li (Journal of Asian Earth Sciences, 2025)

Formation of key aroma compounds in Agrocybe aegerita during hot air drying: Amino acids and reducing sugars identified as flavor precursors - Fan Yang; Erbao Chen; Anzhen Fu; Ye Liu; Shuang Bi (Food Chemistry, 2025)

A smartphone-assisted ultrasensitive colorimetric aptasensor based on DNA-encoded porous MXene nanozyme for visual detection of okadaic acid - Jingtian Chi; Peng Ju; Fan Bi; Siyu Wen; Zhenbo Xiang; Juna Chen; Meng Qiu (Food Chemistry, 2025)

Charged defect management for high-efficiency planar solar cells: Reducing charge recombination and open-circuit voltage loss by employing donor-acceptor molecules to regulate perovskite electronic properties - Miao Yu; Lin Fan; Lixue Wang; Chuanlong Bi; Yuan Gao; Jiadong Liu; Fengyou Wang; Xin Li; Qiong Wu; Xiaoyan Liu; Huilian Liu; Lili Yang (Chemical Engineering Journal, 2025)

Angiopoietin-like protein 2 inhibits thrombus formation - Tiantian Zhang; Mingliang Zhang; Lingyu Guo; Dongsheng Liu; Kandi Zhang; Changlong Bi; Peng Zhang; Jin Wang; Yuqi Fan; Qing He; Alex C. Y. Chang; Junfeng Zhang (Molecular and Cellular Biochemistry, 2025)
Acute myocardial infarction is mainly caused by a lack of blood flood in the coronary artery. Angiopoietin-like protein 2 (ANGPTL2) induces platelet activation and thrombus formation in vitro through binding with immunoglobulin-like receptor B, an immunoglobulin superfamily receptor. However, the mechanism by which it regulates platelet function in vivo remains unclear. In this study, we investigated the role of ANGPTL2 during thrombosis in relationship with ST-segment elevation myocardial infarction (STEMI) with spontaneous recanalization (SR). In a cohort of 276 male and female patients, we measured plasma ANGPTL2 protein levels. Using male Angptl2 -knockout and wild-type mice, we examined the inhibitory effect of Angptl2 on thrombosis and platelet activation both in vivo and ex vivo. We found that plasma and platelet ANGPTL2 levels were elevated in patients with STEMI with SR compared to those in non-SR (NSR) patients, and was an independent predictor of SR. Angptl2 deficiency accelerated mesenteric artery thrombosis induced by FeCl 3 in Angptl2 –/– compared to WT animals, promoted platelet granule secretion and aggregation induced by thrombin and collogen while purified ANGPTL2 protein supplementation reversed collagen-induced platelet aggregation. Angptl2 deficiency also increased platelet spreading on immobilized fibrinogen and clot contraction. In collagen-stimulated Angptl2 –/– platelets, Src homology region 2 domain–containing phosphatase (Shp)1-Y564 and Shp2-Y580 phosphorylation were attenuated while Src, Syk, and Phospholipase Cγ2 (PLCγ2) phosphorylation increased. Our results demonstrate that ANGPTL2 negatively regulated thrombus formation by activating ITIM which can suppress ITAM signaling pathway. This new knowledge provides a new perspective for designing future antiplatelet aggregation therapies.

Land rights, resource allocation and urban settlement choices of migrant workers in Yunnan, Western China - Youqing Fan; Mengtao Gao; Lanlan Bi; Chyi Lin Lee; Guangbo Yin (Land Use Policy, 2025)

Exposure to multiple metals and leukocyte telomere length in children and adolescents: The mediating effect of thyroid hormones - Qing Liu; Gaojie Fan; Jianing Bi; Qing Fang; Fei Luo; Xiaofeng Huang; Heng Li; Binghai Liu; Lianyan Yan; Wenwen Guo; Liqin Hu; Surong Mei; et al. (Environmental Research, 2025)

Fenofibrate induces liver enlargement in aging mice via activating the PPARα-YAP signaling pathway - Huilin Li; Yanying Zhou; Chenghui Cai; Hangfei Liang; Xuan Li; Min Huang; Shicheng Fan; Huichang Bi (Chemico-Biological Interactions, 2025)

Blocking the PD-1 signal transduction by occupying the phosphorylated ITSM recognition site of SHP-2 - Wenjie Li; Wenyi Mei; Hewei Jiang; Jie Wang; Xiaoli Li; Lina Quan; Yanyan Diao; Yanni Ma; Sisi Fan; Zhuwei Xie; Mengdie Gong; Huan Zhu; et al. (Science China Life Sciences, 2025)

Acid-etched halloysite and Co-Ni-B composites for high-performance supercapacitor application - Fan Yang; Xue-Jing Ma; Jun-Hu Liu; Bi Chen; Kang Yang; Xin-Yu Liu; Wei-Bin Zhang (Applied Clay Science, 2025)

Genetic diversity and genetic structure of local pear cultivars in Xinjiang based on SNP markers - Qingrui Bi; Dongsheng Cui; Guoquan Fan; Shikui Zhang; Shaopeng Wang; Yingying Niu; Shirong Zhao (South African Journal of Botany, 2024)

Biomagnification of polybrominated diphenyl ethers and alternative halogenated flame retardants through food chains of yellowfin tuna (Thunnus albacares) and their prey from the South China Sea and the associated potential health risk - Run-Xia Sun; Chang-Gui Pan; Feng-Jiao Peng; Zhong-Biao Chen; Yue Sun; Jiang-Tao Fan; Jun Zhang; Bi-Xian Mai (Science of The Total Environment, 2024)

A novel improved actuator line method for tandem-arranged wind turbines wake analysis and its application - Ning Fan; Xianxu Yuan; Wenyang Duan; Lin Bi (Ocean Engineering, 2024)

Research on chromium removal mechanism by electrochemical method from wastewater - Jianfeng Wan; Menglin Yu; Wenyan Bi; Yihong Sun; Wei Wang; Yikai Hou; Shizheng Xie; Tianen Li; Yunchang Fan (Journal of Water Process Engineering, 2024)

Association between multiple metals exposure and metabolic dysfunction-associated fatty liver disease among Chinese adults - Qing Liu; Jianing Bi; Gaojie Fan; Mingyang Wu; Xiya Qin; Qing Fang; Surong Mei; Zhengce Wan; Yongman Lv; Lulu Song; Youjie Wang (Journal of Trace Elements in Medicine and Biology, 2024)

Late mesozoic exhumation of silurian – Devonian and permian Ni-Co sulfide deposits in the East Kunlun orogenic belt: Constraints from zircon fission track ages - Xueyu Yan; Yuxin Fan; Qingsong Cai; Minmin Gao; Dengdong Lu; Ke Bi; Chuanying Zhu; Mingjie Zhang; Ying Wang; Guangliang Yang; Xiaohu Li; Buqing Wang (Journal of Geochemical Exploration, 2024)

QTL mapping and genome-wide association analysis reveal genetic loci and candidate gene for resistance to gray leaf spot in tropical and subtropical maize germplasm - Yanhui Pan; Fuyan Jiang; Ranjan K. Shaw; Jiachen Sun; Linzhuo Li; Xingfu Yin; Yaqi Bi; Jiao Kong; Haiyang Zong; Xiaodong Gong; Babar Ijaz; Xingming Fan (Theoretical and Applied Genetics, 2024)

Sex-Specific Associations Between Organophosphate Esters Metabolites and Metabolic Dysfunction-Associated Fatty Liver Disease in Chinese Adults - Qing Liu; Gaojie Fan; Jianing Bi; Xiya Qin; Qing Fang; Mingyang Wu; Surong Mei; Zhengce Wan; Yongman Lv; Youjie Wang; Lulu Song; Hui Chen (Exposure and Health, 2024)

Evaluation and comparison of iohexol elimination by UV/peroxymonosulfate and UV/persulfate processes: Radical roles, influence factors and iodinated trihalomethanes formation - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Fan Lai; Yu-Qiong Gao; Yan Ma; Zi-Han Feng; Zi-Jian Yao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2024)

Efficient PPCPs removal from wastewaters via a novel A/O-MBBR system: Transition towards circular economy in the water sector - Xiaowan Dong; Fangshu Wang; Shixin Yu; Jie Lan; Xing Fan; Xiaolin Zhou; Wei Wei; Guo Li; Lihua Cheng; Xuejun Bi; Ruibo Hu; Dong Chen (Journal of Environmental Management, 2024)

VCAT: an integrated variant function annotation tools - Bi Huang; Cong Fan; Ken Chen; Jiahua Rao; Peihua Ou; Chong Tian; Yuedong Yang; David N. Cooper; Huiying Zhao (Human Genetics, 2024)

Association between multiple metal exposure and bone mineral density among Chinese adults - Gaojie Fan; Qing Liu; Mingyang Wu; Jianing Bi; Xiya Qin; Qing Fang; Surong Mei; Zhengce Wan; Yongman Lv; Lulu Song; Youjie Wang (Environmental Geochemistry and Health, 2024)

A double-level analytical framework for understanding waste management policy evolution in China - Quande Qin; Zhibin Wen; Canpeng Huang; Wulin HU; Bi Fan (Environment, Development and Sustainability, 2024)

Roof greening in major Chinese cities possibly afford a large potential carbon sink - Chao Yang; Yinghui Zhang; Min Chen; Song Zhu; Yuzhi Tang; Zhixin Zhang; Wei Ma; Huizeng Liu; Junyi Chen; Bohui Tang; Dejin Zhang; Zhengdong Huang; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Plasma-induced surface interactions of Pd/SrTiO3 catalyst for improved performance of photocatalytic degradation of toluene - Dongliang Gao; Bingwei Wang; Jingyue Bi; Fan Xue; Mifen Cui; Zhaoyang Fei; Lei Li; Xu Qiao (Journal of Environmental Chemical Engineering, 2024)

Quantification- and structural-taste intensity of umami peptides from Agrocybe aegerita through quantitative structure-activity relationship - Fan Yang; Hongyan Meng; Anzhen Fu; Ye Liu; Shuang Bi (Food Chemistry, 2024)

Ecological factors regulate stalk lodging within dense planting maize - Fanlei Kong; Fan Liu; Xiaolong Li; Pijiang Yin; Tianqiong Lan; Dongju Feng; Bi Song; En Lei; Zhong Li; Xinglong Wang; Jichao Yuan (Field Crops Research, 2024)

Association of exposure to multiple metals with hemoglobin levels in Chinese children and adolescents - Fei Luo; Jianing Bi; Qing Liu; Gaojie Fan; Qing Fang; Xiya Qin; Xukuan Zhang; Xiaofeng Huang; Heng Li; Wenwen Guo; Binghai Liu; Lianyan Yan; et al. (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Association between essential metals, adherence to healthy lifestyle behavior, and ankle-brachial index - Xiya Qin; Gaojie Fan; Qing Liu; Mingyang Wu; Jianing Bi; Qing Fang; Surong Mei; Zhengce Wan; Yongman Lv; Lulu Song; Youjie Wang (Journal of Trace Elements in Medicine and Biology, 2024)

Selenium Deficiency Can Promote the Expression of VEGF and Inflammatory Factors in Cartilage Differentiation and Mediates Cartilage Injury - Xiang Meng; Xiumei Meng; Zeju He; Ye Yuan; Yong Fan; Li Yin; Yu Tong; Zheping Hong; Senbo Zhu; Qiong Zhang; Qing Bi (Biological Trace Element Research, 2024)

Temporal accumulation and lag effects of precipitation on carbon fluxes in terrestrial ecosystems across semi-arid regions in China - Haixing Gong; Guoyin Wang; Chenqing Fan; Xianwang Zhuo; Lina Sha; Zexing Kuang; Jianrong Bi; Tiantao Cheng (Agricultural and Forest Meteorology, 2024)

Corrigendum to “Characterization of odor profiles of pea milk varieties and identification of key odor-active compounds by molecular sensory science approaches using soybean milk as a reference” [Food Chemistry 445(2024) 138696] - Lichang Yan; Ying Xu; Fan Yang; Chunhe Shi; Ye Liu; Shuang Bi (Food Chemistry, 2024)

Microbiome dynamics and environment driving factors throughout pit fermentation of Jiang-flavor Baijiu: A multi-omics study - Liangqiang Chen; Fangzhou Li; Fan Yang; Bi Chen; Hai Du; Li Wang; Yan Xu (Food Bioscience, 2024)

Copper Homeostasis Based on Cuproptosis-Related Signature Optimizes Molecular Subtyping and Treatment of Glioma - Siyu Zhang; Huihan Yu; Suling Sun; Xiaoqing Fan; Wenxu Bi; Shuyang Li; Wei Wang; Zhiyou Fang; Xueran Chen (Molecular Neurobiology, 2024)

Mesozoic–Cenozoic exhumation of the giant Jinchuan Ni-Cu sulfide deposit, China: Evidence from single-grain apatite (U-Th)/He ages - Qingsong Cai; Xueyu Yan; Yuxin Fan; Minmin Gao; Guangliang Yang; Ke Bi; Ying Wang; Chuanying Zhu; Mingjie Zhang; Xiaohu Li (Journal of Asian Earth Sciences, 2024)

Characterization of odor profiles of pea milk varieties and identification of key odor-active compounds by molecular sensory science approaches using soybean milk as a reference - Lichang Yan; Ying Xu; Fan Yang; Chunhe Shi; Ye Liu; Shuang Bi (Food Chemistry, 2024)

Identification of candidate gene associated with maize northern leaf blight resistance in a multi-parent population - Yaqi Bi; Fuyan Jiang; Xingfu Yin; Ranjan K. Shaw; Ruijia Guo; Jing Wang; Xingming Fan (Plant Cell Reports, 2024)
Key message QTL mapping combined with genome-wide association studies, revealed a potential candidate gene for resistance to northern leaf blight in the tropical CATETO-related maize line YML226, providing a basis for marker-assisted selection of maize varieties Abstract Northern leaf blight (NLB) is a foliar disease that can cause severe yield losses in maize. Identifying and utilizing NLB-resistant genes is the most effective way to prevent and control this disease. In this study, five important inbred lines of maize were used as parental lines to construct a multi-parent population for the identification of NLB-resistant loci. QTL mapping and GWAS analysis revealed that QTL qtl_YML226_1 , which had the largest phenotypic variance explanation (PVE) of 9.28%, and SNP 5-49,193,921 were co-located in the CATETO-related line YML226. This locus was associated with the candidate gene Zm00001d014471, which encodes a pentatricopeptide repeat (PPR) protein. In the coding region of Zm00001d014471 , YML226 had more specific SNPs than the other parental lines. qRT-PCR showed that the relative expressions of Zm00001d014471 in inoculated and uninoculated leaves of YML226 were significantly higher, indicating that the expression of the candidate gene was correlated with NLB resistance. The analysis showed that the higher expression level in YML226 might be caused by SNP mutations. This study identified NLB resistance candidate loci and genes in the tropical maize inbred line YML226 derived from the CATETO germplasm, thereby providing a theoretical basis for using modern marker-assisted breeding techniques to select genetic resources resistant to NLB.

The reversal of PXR or PPARα activation-induced hepatomegaly - Yifei Zhang; Jie Yang; Shicheng Fan; Yue Gao; Chenghui Cai; Huilin Li; Xuan Li; Xiao Yang; Yunhui Xing; Min Huang; Huichang Bi (Toxicology Letters, 2024)

Climatic background of aeolian sand accumulation in the proximal sandy deserts/lands and its potential genetic linkage with loess in the Chinese Loess Plateau - Minmin Gao; Yuxin Fan; Qingsong Cai; Xueyu Yan; Ke Bi; Chuanying Zhu; Guangliang Yang; Qingsong Zhang (Quaternary International, 2024)

The greener the living environment, the better the health? Examining the effects of multiple green exposure metrics on physical activity and health among young students - Yuheng Mao; Tianyu Xia; Fan Hu; Dan Chen; Yichen He; Xing Bi; Yangcen Zhang; Lu Cao; Jingheng Yan; Jinyu Hu; Yanzi Ren; Hongmei Xu; et al. (Environmental Research, 2024)

Mitochondria-Related Gene MAOB is a Key Biomarker of Osteoarthritis and Inhibition of Its Expression Reduces LPS-induced Chondrocyte Damage - Shiqi Bi; Bo Han; Hongjuan Fan; Yongming Liu; Xuewen Cui (Biochemical Genetics, 2024)

Fe(II)/Fe(III) cycle actuating a novel process to remove organics in waste pit mud from Maotai: Performance and mechanism - Yafei Yang; Jinlai Yuan; Guangxu Bi; Riyu Song; Hezhen Chen; Bi Chen; Fan Yang; Yan Wang; Li Wang (Journal of Water Process Engineering, 2024)

Ball-milled sepiolite/phosphate rock for simultaneous remediation of cadmium-contaminated farmland and alleviation of phosphorus deficiency symptoms in pepper - Jianhua Qu; Yuhui Li; Hebang Sun; Ruixin Liu; Yue Han; Fuxuan Bi; Hongli Fan; Guosheng Zhang; Yupeng Zhang; Yifan Wang; Weidong Cao; Ying Zhang (Chemical Engineering Journal, 2024)

Boosting spring runoff into the sea by reservoir regulation and its potential for estuarine fishery recovery - Xiao Wu; Houjie Wang; Yongyong Fan; Naishuang Bi; Chiyuan Miao; Jingping Xu; Zuosheng Yang (Science China Earth Sciences, 2024)

Oxygen-enriched vacancy spinel Mn-Co oxides by deep thermal reduction for enhanced antibiotics degradation efficiency - Xiai Zhang; Rui Zhou; Ruohong Bi; Tong Wang; Qikui Fan; Hao Zhu; Zhimao Yang; Xiaofei Liu; Chuncai Kong (Journal of Environmental Chemical Engineering, 2024)

Non-volatile taste active compounds and umami evaluation of Agrocybe aegerita hydrolysates derived using different enzymes - Fan Yang; Anzhen Fu; Hongyan Meng; Ye Liu; Shuang Bi (Food Bioscience, 2024)

Identification of a novel marker and its associated laccase gene for regulating ear length in tropical and subtropical maize lines - Yaqi Bi; Fuyan Jiang; Yudong Zhang; Ziwei Li; Tianhui Kuang; Ranjan K. Shaw; Muhammad Adnan; Kunzhi Li; Xingming Fan (Theoretical and Applied Genetics, 2024)
Key message This study revealed the identification of a novel gene, Zm00001d042906 , that regulates maize ear length by modulating lignin synthesis and reported a molecular marker for selecting maize lines with elongated ears. Abstract Maize ear length has garnered considerable attention due to its high correlation with yield. In this study, six maize inbred lines of significant importance in maize breeding were used as parents. The temperate maize inbred line Ye107, characterized by a short ear, was crossed with five tropical or subtropical inbred lines featuring longer ears, creating a multi-parent population displaying significant variations in ear length. Through genome-wide association studies and mutation analysis, the A/G variation at SNP_183573532 on chromosome 3 was identified as an effective site for discriminating long-ear maize. Furthermore, the associated gene Zm00001d042906 was found to correlate with maize ear length. Zm00001d042906 was functionally annotated as a laccase ( Lac4 ), which showed activity and influenced lignin synthesis in the midsection cells of the cob, thereby regulating maize ear length. This study further reports a novel molecular marker and a new gene that can assist maize breeding programs in selecting varieties with elongated ears.

Clay minerals modified nickel boride for electrochemical supercapacitor electrode application - Fan Yang; Xue-Jing Ma; Jing-Lei Yang; Jun-Hu Liu; Bi Chen; Xin-Yu Liu; Kang Yang; Wei-Bin Zhang (Applied Clay Science, 2024)

Characteristics analysis of solid waste generation and carbon emission of beer production in China - Mengqi Fan; Tao Zhou; Ziye Zhao; Yuting Du; Siyan Liu; Zihan Bi; Jiaqi Lu; Hongping He; Lei Li; Xuya Peng; Xiaofeng Gao; Yilu Gu (Environmental Research, 2024)

The effect of microgroove pattern modification combined with MOF coating on titanium alloy for the soft tissue integration of percutaneous implants - Baobao Xue; Sheng Miao; Yue Yuan; Wenbo Geng; Donglin Li; Chao Yang; Jiahao Zeng; Kaiyong Cai; Hongbo Wei; Long Bi; Junjun Fan (Chemical Engineering Journal, 2024)

Study on the improvement of complexation efficiency and anti-digestibility of phenolic acids based on electrospun starch fibers - Haoran Fan; Xu Yao; Zhijun Chen; Ruolan Ma; Yanhong Bi; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Research International, 2024)

Characterization and stabilization of incineration fly ash from a new multi-source hazardous waste co-disposal system: field-scale study on solidification and stabilization - Xiaofan Huang; Lei Wang; Gu Fan; Xiaotao Bi; Dahai Yan; Jonathan W. C. Wong; Yuezhao Zhu (Environmental Science and Pollution Research, 2024)

Associations of polychlorinated biphenyls and organochlorine pesticides with metabolic dysfunction-associated fatty liver disease among Chinese adults: Effect modification by lifestyle - Qing Liu; Gaojie Fan; Jianing Bi; Xiya Qin; Qing Fang; Mingyang Wu; Surong Mei; Zhengce Wan; Yongman Lv; Lulu Song; Youjie Wang (Environmental Research, 2024)

Anthropogenic influence has significantly affected snowfall changes in Eurasia - Wenqing Lin; Huopo Chen; Weiqi Wang; Dawei Zhang; Fan Wang; Wuxia Bi (Atmospheric Research, 2024)

Exposure to organochlorine pesticides and polychlorinated biphenyls, adherence to an ideal cardiovascular health, and arterial stiffness among Chinese adults - Jianing Bi; Qing Liu; Gaojie Fan; Qing Fang; Xukuan Zhang; Xiya Qin; Mingyang Wu; Zhengce Wan; Yongman Lv; Youjie Wang; Lulu Song (Environmental Geochemistry and Health, 2024)

Association of prenatal essential metal exposure with newborn mitochondrial DNA copy number: Results from a birth cohort study - Jianing Bi; Lulu Song; Mingyang Wu; Qing Liu; Luli Xu; Gaojie Fan; Zhongqiang Cao; Chao Xiong; Youjie Wang (Reproductive Toxicology, 2023)

Interplay of shell evolution and oxidation depth on the ignition and combustion behavior of aluminum nanoparticles - Yiming Lu; Lili Ye; Fan Wang; Lei Zhang; Yubo Bi; Haiyong Cong; Mingshu Bi (Fuel, 2023)

The dual role of potassium ferrate in promoting primary sludge hydrolysis and acidogenesis in anaerobic fermentation - Ling Wang; Chang Liu; Xing Fan; Thangavel Sangeetha; Kailing Pan; Xuejun Bi; Wenzong Liu; Xiaoqiu Lin; Xiaodong Wang; Aijie Wang; Heliang Pang (Chemical Engineering Journal, 2023)

Effects of beauvericin on the blood cells of Bombyx mori - Yong Bi; Lingzhi Wu; Baozhen Li; Yanping Hao; Zixiao Li; Jiwei Zhang; Aiying Cheng; Guizhen Yuan; Jinhua Fan (Journal of Invertebrate Pathology, 2023)

Health risk assessment of trace metal(loid)s in agricultural soil using an integrated model combining soil-related and plants-accumulation exposures: A case study on Hainan Island, South China - Bi-gui Lin; Pan Pan; Chao-xian Wei; Xi-chao Chen; Zong-yao Zhang; Qing-fang Fan; Fang Liu; Bei-bei Liu; Lin Wu (Science of The Total Environment, 2023)

Paleozoic rapid denudation of the Proterozoic Jinchuan Ni-Cu-PGE sulfide deposit, NW China: Insights from single-grain zircon (U-Th)/He thermochronology - Qingsong Cai; Yuxin Fan; Xueyu Yan; Ying Wang; Minmin Gao; Guangliang Yang; Mingjie Zhang; Ke Bi; Hongfu Zhang; Xiaohu Li (Journal of Asian Earth Sciences, 2023)

Effect of sourdough on the quality of whole wheat fresh noodles fermented with exopolysaccharide lactic acid bacteria - Yake Du; Zhen Dai; Tingting Hong; Qing Bi; Haoran Fan; Xueming Xu; Dan Xu (Food Research International, 2023)

Identification of two galectin-4 proteins (PcGal4-L and PcGal4-L-CRD) and their function in AMP expression in Procambarus clarkii - Tingyi Luo; Xianfeng Ren; Lixia Fan; Changying Guo; Bingchun Zhang; Jingxiu Bi; Shuai Guan; Mingxiao Ning (Fish & Shellfish Immunology, 2023)

p-Nrf2/HO-1 Pathway Involved in Methamphetamine-induced Executive Dysfunction through Endoplasmic Reticulum Stress and Apoptosis in the Dorsal Striatum - Tao Wei; Jun-Da Li; Yu-Jing Wang; Wei Zhao; Fan Duan; Yan Wang; Ling-Ling Xia; Zhao-Bin Jiang; Xun Song; Yu-Qiong Zhu; Wen-Yi Shao; Ze Wang; et al. (Neurotoxicity Research, 2023)

Associations of polychlorinated biphenyl and organochlorine pesticide exposure with hyperuricemia: modification by lifestyle factors - Gaojie Fan; Qing Liu; Jianing Bi; Qing Fang; Xiya Qin; Mingyang Wu; Yongman Lv; Surong Mei; Youjie Wang; Zhengce Wan; Lulu Song (Environmental Science and Pollution Research, 2023)

The significance of serum Klotho to hearing loss: a potential protector under noise pollution - Jingcheng Zhou; Zheqi Fan; Yiming Bi; Dingchang Li; Xuemin Chen; Kun Hou; Shuaifei Ji (Environmental Science and Pollution Research, 2023)

Mongolia Contributed More than 42% of the Dust Concentrations in Northern China in March and April 2023 - Siyu Chen; Dan Zhao; Jianping Huang; Jiaqi He; Yu Chen; Junyan Chen; Hongru Bi; Gaotong Lou; Shikang Du; Yue Zhang; Fan Yang (Advances in Atmospheric Sciences, 2023)

Exposure to Metal Mixtures and Overweight or Obesity Among Chinese Adults - Gaojie Fan; Qing Liu; Mingyang Wu; Jianing Bi; Xiya Qin; Qing Fang; Zhengce Wan; Yongman Lv; Youjie Wang; Lulu Song (Biological Trace Element Research, 2023)

A new method for long-term in situ monitoring of seabed interface evolution: A self-potential probe - Zhihan Fan; Xianming Zhu; Haibo Xu; Zhiwen Sun; Hong Zhang; Xianbin Bi; Cong Hu; Dequan Lu; Zhongqiang Sun; Kai Li; Yongzheng Quan; Yonggang Jia (Ocean Engineering, 2023)

Investigating food web structure and system function of an artificial reef ecosystem based on carbon and nitrogen stable isotope analysis: implications for reef management - Jie Feng; Xiaolong Zhao; Fan Bi; Wei Zhao; Liang Zhao; Hao Song; Meijie Yang; Zhi Hu; Cong Zhou; Pu Shi; Pengpeng Hu; Peizhen Ma; et al. (Frontiers in Marine Science, 2023)
Introduction Food web is an important basis for identifying trophodynamic processes, and evaluating the structural and functional characteristics of ecosystems. The trophodynamics and system function of artificial reef (AR) ecosystems have rarely been examined. Methods Stable isotope analysis was used to investigate the food web structure and functions of an artificial reef (AR) ecosystem in this study. Results and Discussion The δ13C and δ15N values of particulate organic matter (POM) in AR showed noticeable seasonal changes, and the δ13C value of POM in autumn was significantly higher than that in other seasons (p<0.05). There were no significant seasonal variations in the δ13C values of solid organic matter (SOM), and no significant difference between SOM and POM was observed except in autumn. Moreover, macroalgae did not significantly affect the δ13C values of SOM. Phytoplankton may be the primary nutrient source in the AR ecosystem. The δ13C values of most crustaceans in the AR were approximately between (-17.03 ± 0.22) ‰ – (-17.74 ± 0.07) ‰, higher than those of most fish, indicating that they may have different basal nutrient sources. The trophic level (TL) of invertebrates was between 2.00 and 3.09, and that of fish was between 2.98 and 3.66. The distribution of δ13C and TLs of crustaceans and fish showed that, except for crustaceans, bivalve shellfish and zooplankton might also be important food sources for fish in the AR ecosystem. Conclusion The δ13C and δ15N values of most species in the AR showed good continuity, indicating that they may be mainly produced from the AR ecosystem. Migratory species such as Lateolabrax japonicus and Sepiella maindroni showed higher δ13C values, indicating that they may have migrated from other sea areas. To maintain the stability of the ecosystem structure and function of the AR ecosystem, fishing activities should be carried out following the maximum sustainable yield theory. Future research needs to identify the nutritional relationship between AR and its adjacent sea areas, to depict the food web structure of the AR with higher accuracy.

Sex-specific associations of single metal and metal mixture with handgrip strength: a cross-sectional study among Chinese adults - Xiya Qin; Lulu Song; Gaojie Fan; Qing Liu; Mingyang Wu; Jianing Bi; Qing Fang; Zhengce Wan; Yongman Lv; Youjie Wang (Environmental Science and Pollution Research, 2023)

Metagenomics reveals the increased antibiotics resistome through prokaryote rather than virome after overuse of rare earth element compounds - Alin Song; Jingjing Peng; Zhiyuan Si; Duanyang Xu; Miaomiao Sun; Jiayin Zhang; Sai Wang; Enzhao Wang; Jingjing Bi; Fayao Chong; Fenliang Fan (Science of The Total Environment, 2023)

Deep learning for fluid velocity field estimation: A review - Changdong Yu; Xiaojun Bi; Yiwei Fan (Ocean Engineering, 2023)

Cooking methods effectively alter perfluoroalkyl substances and nutrients in cultured and wild bullfrogs - Qiongping Sun; Jiaer Zhang; Tieyu Wang; Yonglong Xiong; Xinyi Zhan; Hancheng Zhao; Jianwen Wang; Yueyao Fan; Ran Bi; Shuqing Wang; Seongjin Hong; Jong Seong Khim (Journal of Hazardous Materials, 2023)

Can human activities enhance the trade-off intensity of ecosystem services in arid inland river basins? Taking the Taolai River asin as an example - Ting Zhao; Jinghu Pan; Fan Bi (Science of The Total Environment, 2023)

β-catenin/TCF4 inhibitors ICG-001 and LF3 alleviate BDL-induced liver fibrosis by suppressing LECT2 signaling - Yue Gao; Shicheng Fan; Pengfei Zhao; Huilin Li; Chenghui Cai; Xuan Li; Yanying Zhou; Min Huang; Huichang Bi (Chemico-Biological Interactions, 2023)

Template-induced mesoporous Ni–Al oxide catalysts with tuned physico–chemical properties for the oxidative dehydrogenation of ethane - Lian Kong; Dong Li; Jingying Bi; Xiaoqiang Fan; Zean Xie; Xia Xiao; Zhen Zhao (Chemical Engineering Journal, 2023)

The pre-addition of “blocking” proteins decreases subsequent cellulase adsorption to lignin and enhances cellulose hydrolysis - Jingyun Liu; Jie Wu; Yi Lu; Huaiyu Zhang; Qi Hua; Ran Bi; Orlando Rojas; Scott Renneckar; Senqing Fan; Zeyi Xiao; Jack Saddler (Bioresource Technology, 2023)

Synthesis and biological evaluation of new thiazolyl-urea derivatives as potential dual C-RAF/FLT3 inhibitors - Zhi-Hua Zhang; Bi-Fan Zeng; Zhe-Xue Song; Ying-Yu Yang; Kai-yun Zhang; Xue Du; Lin-lin Zhang; Dong Cai (Medicinal Chemistry Research, 2022)

Long-term trend analysis of wave characteristics in the Bohai Sea based on interpolated ERA5 wave reanalysis from 1950 to 2020 - Jichao Wang; Peidong Sun; Zhihong Liao; Fan Bi; Guiyan Liu (Acta Oceanologica Sinica, 2022)

Two new cytotoxic cycloartane triterpenoids from Aphanamixis polystachya (Wall.) R. N. Parker - Yi-ting Wang; Shi-rui Fan; Jie-yun Cai; Jing-jing Guo; Xin-fang Zhang; Bi-juan Yang; Xiao-jiang Hao; Duo-zhi Chen (Natural Product Research, 2022)

CmPMRl and CmPMrs are responsible for resistance to powdery mildew caused by Podosphaera xanthii race 1 in Melon - Haonan Cui; Chao Fan; Zhuo Ding; Xuezheng Wang; Lili Tang; Yingdong Bi; Feishi Luan; Peng Gao (Theoretical and Applied Genetics, 2022)

Migration and abiotic transformation of estrone (E1) and estrone-3-sulfate (E1-3S) during soil column transport - Banghao Du; Weiwei Yu; Lun Yang; Gongduan Fan; Shuo Yang; Hui Jiang; Shenglan Bi; Cheng Yu (Environmental Geochemistry and Health, 2022)

Surface radiation characteristics and downward cloud radiative forcing in southern Xinjiang during summer 2019 - Jianrong Bi; Dapeng Zuo; Fan Yang; Linhan Zhang; Zhongwei Huang; Tianhe Wang (Meteorology and Atmospheric Physics, 2022)

Addition of humic acid accelerates the growth of Euglena pisciformis AEW501 and the accumulation of lipids - Panpan Fan; Pingping Xu; Yuxuan Zhu; Xiaojie Tu; Gaofei Song; Yanxia Zuo; Yonghong Bi (Journal of Applied Phycology, 2022)

Soil bacterial communities interact with silicon fraction transformation and promote rice yield after long-term straw return - Alin Song; Zimin Li; Yulin Liao; Yongchao Liang; Enzhao Wang; Sai Wang; Xu Li; Jingjing Bi; Zhiyuan Si; Yanhong Lu; Jun Nie; Fenliang Fan (Soil Ecology Letters, 2021)

Topography of Visual Features in the Human Ventral Visual Pathway - Shijia Fan; Xiaosha Wang; Xiaoying Wang; Tao Wei; Yanchao Bi (Neuroscience Bulletin, 2021)

Hydrolysis Kinetics of a Novel 3,4-Dichloroisothiazole Plant-Activator Candidate LY5-24-2 by UPLC-Q-TOF - Shuangyu Song; Chengkui Qiao; Lijun Han; Hanzhong Xie; Yingying Bi; Fayi Qin; Qifan Wu; Yuedong Li; Zhijin Fan (Bulletin of Environmental Contamination and Toxicology, 2021)

Development and application of a novel triplex protein microarray method for rapid detection of antibodies against avian influenza virus, Newcastle disease virus, and avian infectious bronchitis virus - Yuan Li; Jianhua Hu; Jing Lei; Wentao Fan; Zhenwei Bi; Suquan Song; Liping Yan (Archives of Virology, 2021)

Spatial and temporal characteristics of surface albedo in Badain Jaran Desert, China - Peng He; Lishuai Xu; Rutian Bi; Fan Yang; Zhilei Zhen (Earth Science Informatics, 2021)

Investigation of the Starting-Up Axial Hydraulic Force and Structure Characteristics of Pump Turbine in Pump Mode - Zhongyu Mao; Ran Tao; Funan Chen; Huili Bi; Jingwei Cao; Yongyao Luo; Honggang Fan; Zhengwei Wang (Journal of Marine Science and Engineering, 2021)
During the starting up of the pump mode in pump turbines, the axial hydraulic force acting on the runner would develop with the guide vane opening. It causes deformation and stress on the support bracket, main shaft and runner, which influence the operation security. In this case, the axial hydraulic force of the pump turbine is studied during the starting up of pump mode. Its influences on the support bracket and main shaft are investigated in detail. Based on the prediction results of axial hydraulic force, the starting-up process can be divided into “unsteady region” and “Q flat region” with obviously different features. The mechanism is also discussed by analyzing pressure distributions and streamlines. The deformation of the support bracket and main shaft are found to have a relationship with the resultant force on the crown and band. A deflection is found on the deformation of the runner with the nodal diameter as the midline in the later stages of the starting-up process. The reason is discussed according to pressure distributions. The stress concentration of the support bracket is found on the connection between thrust seating and support plates. The stress of the runner is mainly on the connection between the crown and the blade’s leading-edge. This work will provide more useful information and strong references for similar cases. It will also help in the design of pump turbine units with more stabilized systems for reducing over-loaded hydraulic force, and in the solving of problems related to structural characteristics.

A forecasting model for wave heights based on a long short-term memory neural network - Song Gao; Juan Huang; Yaru Li; Guiyan Liu; Fan Bi; Zhipeng Bai (Acta Oceanologica Sinica, 2021)

Two new bioactive lignans from leaves and twigs of Cleistanthus concinnus Croizat - Shi-rui Fan; Jing-jing Guo; Yi-ting Wang; Bi-juan Yang; Duo-zhi Chen; Xiao-jiang Hao (Natural Product Research, 2020)

The TOR pathway participates in the regulation of growth development in juvenile spotted drum (Nibea diacanthus) under different dietary hydroxyproline supplementation - Hua Rong; Fan Lin; Yunlong Zhang; Baoliang Bi; Tengfei Dou; Xiangwei Wu; Jude Juventus Aweya; Xiaobo Wen (Fish Physiology and Biochemistry, 2020)

Adaptive feeding in the American oyster Crassostrea virginica : Complex impacts of pulsatile flow during pseudofecal ejection events - Linlin Wang; Junting Song; Hongsheng Bi; Matthew Gray; Chunlei Fan; Ming Liu; Xian‐Zhong Mao (Limnology and Oceanography, 2020)
Adaptive feeding is a strategy used by many organisms to maintain growth and reproduction success while encountering varying feeding conditions. Oysters are sessile benthic and non‐siphon filter feeders. Oysters are well adapted to modify the ambient microenvironment through their pumping behavior and particle selection activity. Rejection of unsuitable food particulates bound in pseudofeces via ejection events are an integral part of oyster feeding during which oysters produced strong flow opposite to their inhalant feeding flow. The strong opposite pulsatile flow during the ejection event inevitably disrupts the oyster's normal feeding cycle, but how oysters restart their feeding and allocate their energy consumption during an ejection event has not been investigated. The present study used particle image velocimetry (PIV) to examine the impact of ejection events on the feeding of the American oyster, Crassostrea virginica . The strong pulsatile flow resulting from pseudofecal ejection altered the external flow fields by moving water away from the shell. The initial feeding zone after pseudofecal ejection was relatively narrow, possessed a low pulsatile flow, and did not exploit the full flow field. The feeding zone gradually expanded as the pulsatile flow weakened. The strong shear rate at the stable feeding zone then sustained the feeding flow that facilitated oyster feeding. Furthermore, the volumetric fluxes often increased after the ejection event, suggesting increase in feeding efficiency after ejection events. These PIV studies provide new insight on the interactions between feeding oysters and the surrounding physical environment at small yet ecologically relevant scales.

Ring-widths of Abies at tree-line ecotone reveal three centuries of early winter season temperature changes in Yunnan, China - Yingfeng Bi; Whitney Cory; Zenxin Fan; Jingchao Yang; Zhikun Wu; Wei Huang; Jianwen Li; Xuefei Yang (Climate Dynamics, 2020)
Variation in winter temperature is less well understood than in annual and summer temperatures over long timescales, particularly in low-latitude (0–30° N) montane regions with large spatial and topographic heterogeneity. Understanding these variations could be critical for forest manageemnt in these important tree growing regions. We collected tree-ring cores from Yunnan Province in montane southwest China, to determine how winter temperature has varied in the past and to explore its possible drivers in this region. Six highly correlated site chronologies were combined into a long and well-replicated regional composite (RC) chronology. The RC chronology correlated strongest with mean early winter season temperature (EWST) from November to January during 1959–2015. We applied RC chronology to reconstruct EWST from 1653 to 2015. The reconstruction shows five relatively warm historic intervals (1658–1718, 1743–1755, 1771–1791, 1929–1959, and 1995–2015) and cold intervals (1720–1742, 1792–1852, 1860–1883, 1905–1928, and 1960–1994). The 1950s with six anomalous warm seasons and 1980s with five anomalous cold seasons were the warmest and coldest decades, respectively. The EWST reconstruction generally agreed with other winter temperature reconstructions from nearby areas and with historical documents. Atlantic Multidecadal Oscillation (AMO) might be a key forcing of multidecadal winter temperature variations in montane southwest China over the past three and half centuries. Both warm and cold temperature periods coincide with respective positive and negative phases of AMO. Besides, the cold intervals during the nineteenth and twentieth centuries may also have been influenced by large volcano eruptions in low-latitude regions of south and east Asia. Our EWST reconstruction not only improves our understanding of the trends and variations of winter climate history, but also supports planning for resilience in conservation, agriculture, and forestry management in montane southwest China into the future.

Effects of Waterborne Cadmium Exposure on Its Internal Distribution in Meretrix meretrix and Detoxification by Metallothionein and Antioxidant Enzymes - Yao Huang; Hongchao Tang; Jianyu Jin; Meng bi Fan; Alan K. Chang; Xueping Ying (Frontiers in Marine Science, 2020)

Characterization of a major quantitative trait locus on the short arm of chromosome 4B for spike number per unit area in common wheat (Triticum aestivum L.) - Jinghui Li; Shaozhe Wen; Chaofeng Fan; Minghu Zhang; Shuai Tian; Wenjing Kang; Wenxin Zhao; Chan Bi; Qiuyan Wang; Shuang Lu; Weilong Guo; Zhongfu Ni; et al. (Theoretical and Applied Genetics, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Spatio-temporal variability of phytoplankton assemblages and its controlling factors in spring and summer in the Subei Shoal of Yellow Sea, China - Yuanzi Huo; Honghua Shi; Jianheng Zhang; Qiao Liu; Yuanliang Duan; Qing He; Kefeng Yu; Hongsheng Bi; Chunlei Fan; Peimin He (Acta Oceanologica Sinica, 2019)

Feeding modes shape the acquisition and structure of the initial gut microbiota in newborn lambs - Yanliang Bi; Madison S. Cox; Fan Zhang; Garret Suen; Naifeng Zhang; Yan Tu; Qiyu Diao (Environmental Microbiology, 2019)
Summary Early gut microbial colonization is important for postnatal metabolic and immune development. However, little is known about the effects of different feeding modes (suckling versus bottle‐feeding) or microbial sources on this process in farm animals. We found that suckled and bottle‐fed newborn lambs had their own distinct gut microbiota. Results from 16S rRNA gene sequencing and qPCR showed that, compared with suckling, bottle feeding significantly increased the abundances of Escherichia/Shigella , Butyricicoccus , and Clostridium XlVa, while significantly decreased the abundance of Clostridium XI. The higher levels of Escherichia/Shigella in bottle‐fed lambs suggest that artificial feeding may increase the number of potential pathogens and delay the establishment of the anaerobic environment and anaerobic microbes. Feeding modes also affected the direct transmission of bacteria from the mother and the environment to newborns. The SourceTracker analysis estimated that the early gut microbes of suckled lambs were mainly derived from the mother's teats (43%) and ambient air (28%); whereas those of bottle‐fed lambs were dominated by bacteria from the mother's vagina (46%), ambient air (31%), and the sheep pen floor (12%). These findings advance our understanding of gut microbiota in early life and may help design techniques to improve gut microbiota and health.

Pharmacokinetic behaviors of ligustrazine after single- and multiple-dose intravenous Shenxiong glucose injection in rats by high-performance liquid chromatography - Qiong Wang; Huaping Sun; Li Yu; Xianpeng Ma; Baoping Jiang; Changqiong Bi; Zhihua Wang; Qinghong Fan; Yuan Yu; Yueheng Liu; Hong Nie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Climate and extrema of ocean waves in the East China Sea - Hailun He; Jinbao Song; Yefei Bai; Yao Xu; Juanjuan Wang; Fan Bi (Science China Earth Sciences, 2018)

Sea surface wind speed and sea state retrievals from dual-frequency altimeter and its preliminary application in global view of wind-sea and swell distributions - Shuiqing Li; Hui Shen; Yijun Hou; Yijun He; Fan Bi (International Journal of Remote Sensing, 2018)

Synthesis and anticonvulsant activity of some novel 7-(benzylamino) -1H-benzo[b][1,4]diazepine-2,4(3H, 5H)-dione derivatives - Yun-Peng Shao; Rong-Bi Han; Hui-Fan Wu; Feng-Yu Piao (Medicinal Chemistry Research, 2018)

Increasing winter conductive heat transfer in the Arctic sea-ice-covered areas: 1979–2014 - Xieyu Fan; Haibo Bi; Yunhe Wang; Min Fu; Xuan Zhou; Xiuli Xu; Haijun Huang (Journal of Ocean University of China, 2017)

Characterization and physical mapping of nuclear ribosomal RNA (rRNA) genes in the haploid gametophytes of Saccharina japonica (Phaeophyta) - Li Liu; Qi-Fan Yang; Wu-Shan Dong; Yan-Hui Bi; Zhi-Gang Zhou (Journal of Applied Phycology, 2017)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

mtDNA Heteroplasmy in Monozygotic Twins Discordant for Schizophrenia - Hong Li; Rui Bi; Yu Fan; Yong Wu; Yanqing Tang; Zongchang Li; Ying He; Jun Zhou; Jinsong Tang; Xiaogang Chen; Yong-Gang Yao (Molecular Neurobiology, 2017)

Erratum to: Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features - Jing Zhang; Tomasz Gambin; Bo Yuan; Przemyslaw Szafranski; Jill A. Rosenfeld; Mohammed Al Balwi; Abdulrahman Alswaid; Lihadh Al-Gazali; Aisha M. Al Shamsi; Makanko Komara; Bassam R. Ali; Elizabeth Roeder; et al. (Human Genetics, 2017)

Performance of the matrix-assisted laser desorption ionization time-of-flight mass spectrometry system for rapid identification of streptococci: a review - W.-T. Fan; T.-T. Qin; R.-R. Bi; H.-Q. Kang; P. Ma; B. Gu (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

The OPA1 Gene Mutations Are Frequent in Han Chinese Patients with Suspected Optic Neuropathy - A-Mei Zhang; Rui Bi; Qiu-Xiang Hu; Yu Fan; Qingjiong Zhang; Yong-Gang Yao (Molecular Neurobiology, 2017)

Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features - Jing Zhang; Tomasz Gambin; Bo Yuan; Przemyslaw Szafranski; Jill A. Rosenfeld; Mohammed Al Balwi; Abdulrahman Alswaid; Lihadh Al-Gazali; Aisha M. Al Shamsi; Makanko Komara; Bassam R. Ali; Elizabeth Roeder; et al. (Human Genetics, 2017)

The temporal and spatial variations in the Pacific wind and wave fields for the period 2002–2011 - Yao Xu; Fan Bi; Jinbao Song; Hailun He (Acta Oceanologica Sinica, 2017)

Novel mutations in quinolone resistance-determining regions of gyrA, gyrB, parC and parE in Shigella flexneri clinical isolates from eastern Chinese populations between 2001 and 2011 - T. Qin; R. Bi; W. Fan; H. Kang; P. Ma; B. Gu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Copper partitioning between granitic silicate melt and coexisting aqueous fluid at 850 °C and 100 MPa - Shuilong Wang; Hui Li; Linbo Shang; Xianwu Bi; Xinsong Wang; Wenlin Fan (Acta Geochimica, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Photosynthesis, antioxidant system and gene expression of bermudagrass in response to low temperature and salt stress - Ao Liu; Zhengrong Hu; Aoyue Bi; Jibiao Fan; Margaret Mukami Gitau; Erick Amombo; Liang Chen; Jinmin Fu (Ecotoxicology, 2016)

PLD3 in Alzheimer’s Disease: a Modest Effect as Revealed by Updated Association and Expression Analyses - Deng-Feng Zhang; Yu Fan; Dong Wang; Rui Bi; Chen Zhang; Yiru Fang; Yong-Gang Yao (Molecular Neurobiology, 2016)

Seafood consumption among Chinese coastal residents and health risk assessment of heavy metals in seafood - Ran Zhao; Shuangshuang Yan; Min Liu; Bi Wang; Dong Hu; Dongbei Guo; Juan Wang; Wanting Xu; Chun Fan (Environmental Science and Pollution Research, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

RETRACTED ARTICLE: Relationship of Serum Heart-Type Fatty Acid-Binding Protein Levels and Cerebral Infarction: a Meta-analysis - Bao-Liang Sun; Ming-Feng Yang; Xiao-Yi Yang; Jing-Yi Sun; Da-Wei Li; Zong-Yong Zhang; Lei-Lei Mao; Cun-Dong Fan; Cheng-Bi Zheng; Hong-Li Gao; Feng-Ze Wang; Feng Zhang; et al. (Molecular Neurobiology, 2015)

Disruption of thalamic connectivity in Alzheimer’s disease: a diffusion tensor imaging study - Qing-Yong Zhu; Si-Wei Bi; Xiu-Ting Yao; Zhi-Yan Ni; Ying Li; Bo-Yu Chen; Guo-Guang Fan; Xiu-Li Shang (Metabolic Brain Disease, 2015)

Evaluation of the simulation capability of the Wavewatch III model for Pacific Ocean wave - Fan Bi; Jinbao Song; Kejian Wu; Yao Xu (Acta Oceanologica Sinica, 2015)

Effects of light intensity and quality on phycobiliprotein accumulation in the cyanobacterium Nostoc sphaeroides Kützing - Rui Ma; Fan Lu; Yonghong Bi; Zhengyu Hu (Biotechnology Letters, 2015)

Cytotoxin-induced NADPH oxides activation: roles in regulation of cell death - Yongtao Zhang; Xiaolei Bi; Fan Jiang (Archives of Toxicology, 2015)

Combining Bone Marrow Stromal Cells with Green Tea Polyphenols Attenuates the Blood-Spinal Cord Barrier Permeability in Rats with Compression Spinal Cord Injury - De-shui Yu; Li-bo Liu; Yang Cao; Yan-song Wang; Yun-long Bi; Zi-jian Wei; Song-ming Tong; Gang Lv; Xi-fan Mei (Journal of Molecular Neuroscience, 2015)

MTBP inhibits migration and metastasis of hepatocellular carcinoma - Qian Bi; Atul Ranjan; Rui Fan; Neeraj Agarwal; Danny R. Welch; Steven A. Weinman; Jie Ding; Tomoo Iwakuma (Clinical & Experimental Metastasis, 2015)

l-Ornithine Schiff base–copper and –cadmium complexes as new proteasome inhibitors and apoptosis inducers in human cancer cells - Zhongyu Zhang; Caifeng Bi; Yuhua Fan; Nan Zhang; Rahul Deshmukh; Xingchen Yan; Xiuwen Lv; Pengfei Zhang; Xia Zhang; Q. Ping Dou (JBIC Journal of Biological Inorganic Chemistry, 2015)

Regulatory mechanism of ZNF139 in multi-drug resistance of gastric cancer cells - Yong Li; Bi-bo Tan; Qun Zhao; Li-qiao Fan; Yü Liu; Dong Wang (Molecular Biology Reports, 2014)

Synthesis and anticonvulsant evaluation of some new 1,3,4,5-tetrahydro-6-alkoxy-2H-1-benzazepin-2-one derivatives - Rong-Bi Han; Yun-Peng Shao; Hui-Fan Wu; Duo Zhang; Feng-Yu Piao (Medicinal Chemistry Research, 2014)

Wave effect on the ocean circulations through mass transport and wave-induced pumping - Fan Bi; Kejian Wu (Journal of Ocean University of China, 2014)

Recent advances in the study of testicular nuclear receptor 4 - Xian-fan Ding; Shi-cheng Yu; Bi-de Chen; Shin-jen Lin; Chawnshang Chang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2013)

Improving the estimate of wind energy input into the Ekman layer within the Antarctic Circumpolar Current - Yuming Zhang; Kejian Wu; Xiaoshuang Zhang; Fan Bi; Zhaoyang Song; Shouhua Liu (Acta Oceanologica Sinica, 2013)

1,10-Phenanthroline promotes copper complexes into tumor cells and induces apoptosis by inhibiting the proteasome activity - Zhen Zhang; Caifeng Bi; Sara M. Schmitt; Yuhua Fan; Lili Dong; Jian Zuo; Q. Ping Dou (JBIC Journal of Biological Inorganic Chemistry, 2012)

The effect of Stokes drift on Ekman transport in the open sea - Fan Bi; Kejian Wu; Yuming Zhang (Acta Oceanologica Sinica, 2012)

A new plastic surgical technique for adult congenital webbed penis - Yue-bing Chen; Xian-fan Ding; Chong Luo; Shi-cheng Yu; Yan-lan YU; Bi-de Chen; Zhi-gen Zhang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2012)

Clinical Value of ELISA-MPT64 for the Diagnosis of Tuberculous Pleurisy - Zhonghua Liu; Changtai Zhu; Hua Yang; Haili Hu; Yonghong Feng; Lianhua Qin; Zhenling Cui; Aixiao Bi; Ruijuan Zheng; Ruiliang Jin; Lin Fan; Zhongyi Hu (Current Microbiology, 2012)

A molecular mechanism underlying ovarian dysfunction of polycystic ovary syndrome: hyperandrogenism induces epigenetic alterations in the granulosa cells - Fan Qu; Fang-Fang Wang; Rong Yin; Guo-Lian Ding; Mohamed El-prince; Qian Gao; Bi-Wei Shi; Hui-Hui Pan; Yi-Ting Huang; Min Jin; Peter C. K. Leung; Jian-Zhong Sheng; et al. (Journal of Molecular Medicine, 2012)

Re-expression of miR-21 contributes to migration and invasion by inducing epithelial-mesenchymal transition consistent with cancer stem cell characteristics in MCF-7 cells - Mingli Han; Manran Liu; Yimeng Wang; Zhiqiang Mo; Xiaokai Bi; Zhirong Liu; Yuanming Fan; Xin Chen; Chengyi Wu (Molecular and Cellular Biochemistry, 2012)

Involvement of KATP/PI3K/AKT/Bcl-2 Pathway in Hydrogen Sulfide-induced Neuroprotection Against the Toxicity of 1-methy-4-phenylpyridinium Ion - Xiao-Qing Tang; Yuan-Yuan Zhuang; Li-Li Fan; Heng-Rong Fang; Cheng-Fang Zhou; Ping Zhang; Bi Hu (Journal of Molecular Neuroscience, 2012)

Inhibition of Hydrogen Sulfide Generation Contributes to 1-Methy-4-Phenylpyridinium Ion-Induced Neurotoxicity - Xiao-Qing Tang; Li-Li Fan; Yu-Juan Li; Xin-Tian Shen; Yuan-Yuan Zhuan; Jian-Qin He; Jin-Hua Xu; Bi Hu; Yuan-Jian Li (Neurotoxicity Research, 2011)

Utilization of dry distiller’s grain and solubles as nutrient supplement in the simultaneous saccharification and ethanol fermentation at high solids loading of corn stover - Dexi Bi; Deqiang Chu; Pei Zhu; Chenyang Lu; Chao Fan; Jian Zhang; Jie Bao (Biotechnology Letters, 2011)

A method for generating precise gene deletions and insertions in Escherichia coli - Qi-Ming Zhou; Dong-Jie Fan; Jiang-Bi Xie; Chuan-Peng Liu; Jun-Mei Zhou (World Journal of Microbiology and Biotechnology, 2010)

Generation and characterisation of Tn5-tagged Xanthomonas oryzae pv. oryzae mutants that overcome Xa23-mediated resistance to bacterial blight of rice - Chun-Lian Wang; An-Bi Xu; Ying Gao; Ying-Lun Fan; Yun-Tao Liang; Chong-Ke Zheng; Liang-Qing Sun; Wen-Quan Wang; Kai-Jun Zhao (European Journal of Plant Pathology, 2009)

Determination of total catechins in tea extracts by HPLC and spectrophotometry - Qiang He; Kai Yao; Dongying Jia; Haojun Fan; Xuepin Liao; Bi Shi (Natural Product Research, 2009)

Crystal structure and geometry-optimization study of N-(2-hydroxy-1-naphthaldene)-4-aminoantipyrine - Feng Guo; Caifeng Bi; Yuhua Fan; Aidong Wang; Jiakun Xu; Xia Zhang (Journal of Ocean University of China, 2008)

RhoC is essential for the metastasis of gastric cancer - Na Liu; Guoyun Zhang; Feng Bi; Yanglin Pan; Yan Xue; Yongquan Shi; Liping Yao; Lina Zhao; Yi Zheng; Daiming Fan (Journal of Molecular Medicine, 2007)

Synthesis, characterization and antibacterial activity of new Ln(III) complexes with an unsymmetrical schiff base ligand - BI Caifeng; Yan Liangliang; Fan Yuhua; Zhang Xia; Wang Aidong (Journal of Ocean University of China, 2006)